Experimental Damage Investigation of Composite Plates Subjected to Impact Loading Conditions - Mohd Sohaimi, Risby (2003)
The use of synthetic fibers such as glass fiber and aramid fiber carbon fiber as composite reinforcement is being increasingly applied in high performance applications since they provide certain advantage of specific high strength and stiffness as compared to metallic materials. In contrast, implementation of natural fiber as reinforcement has not yet received adequate attention from the research community. This study investigates the damage characterization and impact resistance of synthetic and natural fiber reinforced composite square plates subjected to the changes of impact loading and width over thickness (bId) ratio of the composite. For low velocity impact, the testing was performed using Dynatup 8250 equipped with GRC 930-1 Data Interpretation System on fabricated square plates with different impact energy levels and velocities. The severity of impact damage is macroscopically and microscopically investigated. A compressed gas gun equipped with velocity measurement system was designed and fabricated in order to facilitate the high velocity impact testing experimentations. From the results, it has been found that mechanical and impact properties of EFBC and CFC do not posses toughness and modulus as high as GRC. Although EFBC and CFC specimens eXllibit total perforation to the specimens at most impact velocities, EFBC specimen with plate thickness of 8 millimetres was found to have penetration resistance at 22 joules of impact energy level. This is due the performance of Coir as reinforcement in polymer composites is unsatisfactory and not comparable with other natural fibers due to its mechanical properties. It can also be conclude that the impact response of EFBC and CFC specimen chances significantly as the composite thickness increases. Impact damage was found to be in the forms of matrix cracking, fiber fracture and perforation. This study results can be a valuable reference in designing of lightweight composite structure and in developing a better understanding of test methods used to characterize impact behaviours.